FORMATION OF LINGUOCULTUROLOGICAL COMPETENCE IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (ON THE BASIS OF RUSSIAN FAIRY TALES) - Eskaraeva Gulmira Beketovna (Journals Park Publishing, 2023)
Great opportunities for the linguistic and mental development of students include teaching the grammar of the native language, which enriches them with knowledge of the basic laws and rules of the language system, morphological and syntactic means of expressing thoughts, contributes to the development of logical thinking of students, and is the basis for the formation of practical speech and spelling skills. The desire to find ways to resolve these contradictions determined the problem of our study in theoretical terms, the problem of developing a model for the formation of students' language competence in the process of studying syntactic norms, and in practical terms, the problem of creating methodological support for the formation of students' language competence.
Keywords: action producer, actor, speaker, object, thought, carrier, sign, knowledge, vocabulary, grammar, ability, perceive, text.